Toxicity of carbamates to insects - Weiden, M. H. J. (1971)
The discovery of effective insecticidal materials among the carbamic-acid esters is surveyed to provide insight into some of the factors leading to the development of new control agents. Problems associated with attempts to correlate insecticidal activity with acetylcholinesterase inhibition are outlined. The intoxication syndrome is described and its toxicological significance discussed. Structure—activity profiles are presented for selected compounds to illustrate the biological effects produced by structural variations. Categories of carbamates in which no significant insecticidal activity has been discovered are also listed.